2019
DOI: 10.1016/j.scitotenv.2019.03.260
|View full text |Cite
|
Sign up to set email alerts
|

Agro-industrial residues as a unique support in a sand filter to enhance the bioactivity to remove microcystin-Leucine aRginine and organics

Abstract: et al., Agro-industrial residues as a unique support in a sand filter to enhance the bioactivity to remove microcystin-leucine aRginine and organics, Science of the Total Environment,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…CV assay and MTT assay were performed to quantify the biomass and live cells present in the biofilm, respectively. The protocol for the same is mentioned in our previous study (Kumar et al, 2019). Negative control comprised the sand composite materials passed using tap water (not the nutrient-biocell solution) and positive control comprised Staphylococcus epidermidis which is known as a good biofilm former (Chusri et al, 2012).…”
Section: Biofilm Forming Ability Of Different Microcystin-degraders Over Various Sand Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…CV assay and MTT assay were performed to quantify the biomass and live cells present in the biofilm, respectively. The protocol for the same is mentioned in our previous study (Kumar et al, 2019). Negative control comprised the sand composite materials passed using tap water (not the nutrient-biocell solution) and positive control comprised Staphylococcus epidermidis which is known as a good biofilm former (Chusri et al, 2012).…”
Section: Biofilm Forming Ability Of Different Microcystin-degraders Over Various Sand Compositesmentioning
confidence: 99%
“…ALso, the other three references namely, Fayad et al 2015, Gupta et al, 2012 is added. Naghdi et al can be deleted, in place, we have added another article: Kumar et al 2019, this reference was already in the reference list (Kumar et al, 2019).…”
Section: Declaration Of Competing Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Sizirici et al (2019) investigated the removal of bacteria using modified biosand filters (MBSF) filled with gravels coated with iron oxides (IOCG) and reported that the MBSF‐IOCG system exhibited 90.54–95.84%, 99.0%, and 95.33% removal of turbidity, E. coli , and total coliforms, respectively. Kumar et al (2019) reported that the removal of microcystin‐Leucine arginine (MC‐LR) and organics on sand filters filled with agro‐industrial residues was enhanced due to increasing bioactivity. Terin and Sabogal‐Paz (2019) reported the removal of Microcystis aeruginosa and microcystin ‐LR from water using household slow sand bed and reported greater than 2‐log M. aeruginosa removal; MC‐LR was reduced to <1.0 μg/L.…”
Section: Physical Treatmentmentioning
confidence: 99%
“…Despite these challenges, microorganisms that span multiple phyla and even domains are reported to degrade MCs ( Supplementary Table S1). Further, experiments assessing the biodegradation of MCs which employ natural microbial communities from lakes (Christoffersen et al, 2002;Edwards et al, 2008;Eleuterio and Batista, 2010;Mou et al, 2013;Dziga et al, 2017;Lezcano et al, 2018), drinking water reservoirs (Cousins et al, 1996;Ho et al, 2012), estuary and sea water (Lemes et al, 2008), water treatment facilities (Lam et al, 1995;Saito et al, 2003b;Ma et al, 2014), soil (Miller and Fallowfield, 2001;Bibo et al, 2008;Cao et al, 2018;Redouane et al, 2019), lake sediments (Rapala et al, 1994;Cousins et al, 1996;Chen X. et al, 2010;Song et al, 2014;Li et al, 2016;Zhu et al, 2019) and biofilters (Grützmacher et al, 2002;Ho et al, 2006;Lee et al, 2006;Ho et al, 2007;Hoefel et al, 2009;Ho et al, 2012;Kumar et al, 2019) have demonstrated that biodegradation capacity is seemingly ubiquitous across a wide range of environments and occurs under a variety of conditions (Li et al, 2017). For these reasons, the current literature often refers to biodegradation as the most important route for the disappearance of MCs in nature (Christoffersen et al, 2002;Holst et al, 2003;Chen et al, 2008;Grützmacher et al, 2009;Bukowska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%